Identifikasi Determinan Stunting pada Balita di Daerah Pesisir dan Perdesaan Kabupaten Buton Utara - Harleli, Harleli; Irma, Irma (NHM PRESS, 2023)
Stunting is a condition of failure to thrive in children under five (infants under five years old) due to chronic malnutrition so that the child is too short to grow. The determinants of stunting in toddlers include low birth weight (LBW), exclusive breastfeeding and complete basic immunization. This research is quantitative descriptive. The data used in this study is secondary data on stunting obtained from the Southeast Sulawesi Provincial Health Office and the North Buton District Health Office. The population and samples in this study were data on stunting prevalence, exclusive breastfeeding coverage, LBW history and complete basic immunization coverage which were obtained from the Health Office of North Buton Regency from 2016 to 2020. The results showed the prevalence of stunting in North Buton Regency. in a period of 5 (five) years is volatile with the highest prevalence occurring in 2017 at 44.5% and the lowest occurring in 2018 at 27.7% and is still a health problem. The prevalence of stunting and the percentage of exclusive breastfeeding during the 5 years of observation are directly proportional and the percentage of complete basic immunization during the 5 years of observation is very high and even exceeds the target that has been set. When compared descriptively, this high percentage is not proportional to the prevalence of stunting in coastal and rural areas of North Buton Regency